Synthesis, characterization and in vitro drug release of curcumin loaded cassava starch acetate–poly vinyl alcohol/ closite 30b nanocomposites - DEVI PRASAN MOHANTY; S.K BISWAL (International Journal of Pharma and Bio Sciences, 2017)
The aim of the present study is to examine the feasibility of Manihot esculenta (cassava) starch acetate (CSA)–polyvinyl alcohol (PVA)–Closite30B nanocomposites as controlled drug delivery systems. It is one of the novel drug vehicles which can be used for the controlled release of an anticancer drug curcumin (CUM). Simple nano-precipitation method was used to prepare the carriers CSA–PVA-C30B nanocomposites and they were used for entrapping CUM. The physico chemical properties are studied using FTIR, SEM, TGA and XRD. Also we have to study drug encapsulation efficiency, drug loading capacity and in vitro release of CUM. In finally it was proved that the cross linked CSA-PVA-C30B nanocomposites can be a potential polymeric carrier for cancer treatment.